Pengaruh Seduhan Teh Hijau (Camellia Sinensis) Terhadap Hambatan Pertumbuhan Bakteri Streptococcus Sanguis Penyebab Karies (In Vitro) - Tri Budi Santoso, Heri Tri Budi; , drg. Mahmud Kholifa, MDSc; , drg. Juwita Raditya Ningsih (2017)
Sanguis Streptococcus bacteria are the primary pathogens that can cause dental caries. The purpose of this study was to determine the antibacterial activity of various ncentrations of steeping green tea leaves (Camellia sinensis) against the bacteria Streptococcus sanguis. The method used in this research is the agar diffusion method. This study is divided into 5 groups of treatment group and five repetitions. Each treatment consisted of steeping green tea 17.5%, 35%, 70%, distilled water as a negative control and 0.2% chlorhexidine as a positive control. Analysis of data using ANOVA test of the lane with 95% significance level (α = 0.05) followed by Post Hoc LSD test. hlorhexidine distilled water and 5.38 respectively; 7.51; 9.35; 0.00; and 12.32 mm. Concentration of stepping green tea leaves that divided into 17,5%, 35% and 70% was significantly P=0,00 (P<0,05) differents compare with negative control, and it indicated that green tea leaves had caballity to inhibit activity of Streptococcus sanguis. Keywords: antibacterial inhibition zone, steeping green tea leaves (Camellia sinensis), Streptococcus sanguis